PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERN, DAN PRINSIP PENGELOLAAN KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Survei Pada Pemerintah Daerah Se-Eks. Karesidenan Surakarta) - Febriani, Intan; Sarwono, Aris Eddy; Saptantinah P.A, Dewi (Universitas Slamet Riyadi, 2020)
This study aims to determine the effect of human resource competencies, internal control systems, and the principles of regional financial management on the quality of local government financial reports. This research was conducted using a survey method of the civil apparatus of the Se-Eks regional government. Surakarta Residency. The type of data used is quantitative data. The data source used is primary data. Data collection techniques with interviews, questionnaires, and documentation. The population in this study were all civil servants of the state government of the Se-Eks. Surakarta Residency. The sample used in this study is the state civil apparatus in the regional government accounting department. Surakarta Residency. The sampling technique is done by using purposive sampling method. This research shows that human resource competencies, internal control systems, and regional financial management principles affect the quality of financial statements.